Analytic Functions Related to the Strip Domains Involving Generalized Sălăgean Operator (Analysis in Theory and Applications, 2025)
In the paper, the authors introduce a new subclass of univalent functionsassociated with the strip domains by using the generalized Sălăgean operator. The bounds of coefficients and Fekete-Szegö inequality for functions in this class are obtained. The results presented here extend some of the earlier results.
Keywords: Analytic functions; starlike functions; strip domain; differential subordination; Sălăgean operator.